Relationship between efficiency and risks faced by commercial banks in Thailand / Norhidayu Sanip - Sanip, Norhidayu (2008)
This paper studies the profit efficiency of commercial banks in Thailand and explore the potential connection between banks' risks and profit efficiency by testing for an empirical association between estimated profit efficiency and a small number of correlates related to various types of risk common in banking. This paper used multiple regression method in order to see the relationship between the dependent and independent variables. The performance variety in terms profit for both banks were used as dependent variable and as for independent variables, credit risk; liquidity risk; foreign exchange risk and market risk were used. According to the analysis from the year 2002 to 2007,the liquidity risk, exchange rate risk Id credit risk has a significant level, which means that there are relationship between those risk with the profit, while the market risk is insignificant to the profit. As a conclusion this project paper were succeed in proving the relationship between profit d risks faced by commercial banks especially in Thailand.